Sobibor : a history of a Nazi death camp - Schelvis, Jules (Berg, 2007)
"Auschwitz. Treblinka. The very names of these Nazi camps evoke unspeakable cruelty. Sobibor is less well known, and this book discloses the horrors perpetrated there." "Sent in June 1943 to Sobibor, where his wife and family were murdered, Jules Schelvis has written the first book-length, fully documented account of the camp. He details the creation of the killing centre, its personnel, the use of railways, selections, forced labour, gas chambers, escape attempts and the historic uprising." "In documenting this part of Holocaust history, this well-researched account advances our knowledge and understanding of the Nazi attempt to annihilate the European Jews."--Jacket